1999
DOI: 10.1063/1.124599
|View full text |Cite
|
Sign up to set email alerts
|

Thin gate oxide behavior during plasma patterning of silicon gates

Abstract: We have evidenced an unexpected behavior of thin gate oxide layers (thickness in the range 2–4 nm) exposed to plasma processes developed for the patterning of 0.1 μm silicon gates. During the low-energy overetch step of the process, an oxidation of the bulk underlying silicon takes place, leading to the growth of the gate oxide layer. Experimental results obtained from in situ kinetic and spectroscopic ellipsometry measurements and supported by x-ray photoelectron spectroscopy analyses are presented to highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…Donnelly et al 1 first recognized that plasma grown oxide was responsible for the observed silicon loss in the active area next to an etched polysilicon gate. Vallier et al 2 also studied the oxidation of silicon beneath thin gate oxides. Tuda et al 3 examined the role of by-product redeposition and oxide growth on the thickness of the gate oxide.…”
Section: Introductionmentioning
confidence: 97%
“…Donnelly et al 1 first recognized that plasma grown oxide was responsible for the observed silicon loss in the active area next to an etched polysilicon gate. Vallier et al 2 also studied the oxidation of silicon beneath thin gate oxides. Tuda et al 3 examined the role of by-product redeposition and oxide growth on the thickness of the gate oxide.…”
Section: Introductionmentioning
confidence: 97%
“…The high selectivity is usually obtained in a low bias power, high pressure, HBr/O 2 plasma. When the SiO 2 layer becomes very thin (typically less than 4-5 nm) an oxidation of the underlying silicon substrate can be observed depending on the gate oxide thickness and plasma operating conditions 16 through the thin gate oxide and react with the underlying silicon, forming a 2 to 5 nm plasma grown oxide. Previous studies have shown that this oxide regrowth mechanism is ion assisted and that working under low bias power conditions always minimizes the phenomenon 17 .…”
Section: Silicon Gate Etch Processmentioning
confidence: 99%
“…Donnelly et al 23 and Vallier et al 24 reported that Si oxide grows under the thin gate oxide during the overetch step of poly-Si gate etching process. As the ion energy increases, the wet etching rate increases faster than that using N 2 or Ar plasma treatment.…”
Section: B N 2 O 2 and Ar Plasma Treatments On The Removal Of Crmentioning
confidence: 99%